Making the headlines : news media discourse on terrorism in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Defence and Security Studies at Massey University, New Zealand - Stanbury, Brendan Andrew Usher (Massey University, 2024)
Following the Christchurch terrorist attack in March 2019, the New Zealand Government published protocols governing news media reporting during terrorist and national security events (The Department of Prime Minister and Cabinet, 2021). By establishing these protocols, the New Zealand Government acknowledged the role news media play in the wake of a national security event, including acts of terror. While most the New Zealand research relating to media coverage of contemporary terrorism has focused on the role social media plays, particularly in terms of online radicalization, the relationship between commercial news media and terrorism is underrepresented in the New Zealand context. Through a qualitative examination of three New Zealand case studies – the 1985 bombing of the Rainbow Warrior, the 2019 Christchurch attack, and the 2021 LynnMall attack - this research examines how New Zealand news media responded during these events. Using a hybrid thematic analysis approach that initially drew on inductive and then deductive thematic processes, the research identified and examined three key factors common to each of the case studies: how the news media represented the act of terrorism; how it represented the attacker(s); and the role the news media played in shaping the State’s response. It found that while the news media is generally considered to be an impartial actor in the reporting of terrorist attacks, it is neither neutral nor passive in these instances, providing a potential platform to amplify both the terrorist’s and State’s objectives. While causation is difficult to determine, this research concludes that New Zealand news media’s engagement with terrorism has changed over time. Given the prominence of the media as one of the main conduits for public information, the media now plays a significant role in shaping public perceptions of terrorism in New Zealand, reinforcing the official Government narrative, and providing the means for the Government to generate the social licence needed to introduce reforms. By implication, news media should remain live to the political drivers at play behind official determinations of terrorism so as to remain impartial and report objectively as possible during times of high stress.
Keywords: 470107 Media studies; 440804 Defence studies